مساهمة الإتصال غير الرسمي في تحسين الأداء الوظيفي للفرد بمؤسسة النقل والجر بالسكك الحديدية بسوق أهراس - ثلايجية مريم; شعبوني رحيل (My University, 2022)
Abstract: Communication is considered the beating heart of organizational operations. The success of any organization in achieving its goals is measured by a set of variables, including employee performance and its impact on the ground. Informal communication is one of the challenges facing contemporary organizations. Through this study, we have attempted to shed light on informal communication and how it contributes to improving individual job performance within the Railway Transport and Traction Corporation. This study aims to answer the following main question: • To what extent does informal communication contribute to improving job performance in the Railway Transport Corporation? This question was broken down into the following sub-questions: 1. To what extent do personal relationships contribute to fostering a sense of belonging among individuals? 2. Do personal relationships provide additional information that can be used to improve job performance? 3. Do personal relationships contribute to developing a spirit of cooperation among individuals? 4. To what extent does the interpersonal relationship framework contribute to improving the quality of job performance? In this descriptive study, we relied on the descriptive approach and the questionnaire as the primary tool, using a sample of 35 individuals working at the Souk Ahras Railway Transport and Traction Company. In this study, we reached the following results: We find that personal relationships with colleagues at the Souk Ahras Railway Transport and Traction Company are of great importance in embodying an individual's sense of belonging. Through these relationships, individuals feel self-esteem. Furthermore, interpersonal relationships contribute to building self-confidence among employees. This is due to communication with colleagues, the individual's self-disclosure, and discussing work issues with colleagues through the creation of personal bonds, which earns the trust of colleagues and superiors. When individuals find a receptive ear and mutual interaction, personal relationships foster a spirit of cooperation among individuals. This is achieved by aligning the group's goals with the individual's, harmonizing and coherent among organizational members, and fostering group dynamics. This is due to the organization's unified purpose. If interpersonal relationships are directed toward serving the company's goals, this is considered a human dimension that supports and strengthens relationships and achieves job satisfaction. The technical and technological dimension is evident in the following: Personal relationships contribute to saving time and achieving greater speed in performance. This is due to the fact that personal relationships with friends and colleagues are not subject to conditions and restrictions. They transcend the hierarchical ladder and administrative and formal levels, which may sometimes hinder the rapid transmission of information. Although the system of personal relationships provides an impact on job performance, it is not necessarily always positive. Based on the information obtained by the respondents, personal relationships do not provide a suitable work environment for improving job performance. This is due to the occurrence of an atmosphere of chaos, preoccupation with personal matters, and neglect of the desired goal. This may negatively impact the individual's job performance within the organization. This study concluded with a set of recommendations, the most prominent of which are: _ Activating informal communication within the limits it occupies. _ Achieving integration between formal and informal communication and utilizing them to convey accurate information among workers. _ Benefit from some of the advantages of informal communication, especially regarding information pertaining to workers, which the direct supervisor relies on in his directives, dealings, and strategic vision. _ Rely on informal communication to build relationships between supervisors and workers by eliminating some of the obstacles identified by formal communication, and the supervisor attempts to leverage these relationships within the framework of the organization's goals. Likewise, through informal communication, managers gain insight into the true nature of employee information. Meeting employees in informal settings reveals many of the employee's impressions of the organization, through the suggestions they provide to their managers, which contribute to improving job performance. Attempt to identify leaders of informal communication and work with them when circumstances require it. This helps feed informal communication with facts so that it has something useful to convey, rather than harmful data and rumors. This helps make it a contributor to improving organizational performance, not a hindrance. -------------------------------- ملخص : يعتبر الاتصال القلب النابض لتسير المؤسسات، فنجاح أي منظمة في تحقيق أهدافها يقاس بمجموعة من المتغيرات من بينها الأداء الوظيفي للعاملين وما يؤثر فيه على ارض الواقع ، كالاتصال الغير الرسمي باعتباره احد التحديات التي تواجه المنظمات المعاصرة و من خلال هذه الدراسة قد حاولنا تسليط الضوء على الاتصال غير الرسمي وكيف يساهم هذا الأخير في تحسين الأداء الوظيفي للفرد داخل مؤسسة النقل و الجر بالسكك لحديدية ، وذلك على الإجابة على التساؤل الرئيسي التالي : • إلى أي مدى يساهم الإتصال غير الرسمي في تحسين الأداء الوظيفي في مؤسسة النقل بالسكك الحديدية ؟ وقد تم تفكيك هذا التساؤل إلى التساولات الفرعية التالية : 1_ ما مدى مساهمة العلاقات الشخصية في تحقيق روح الانتماء لدى الأفراد ؟ 2_ هل توفر العلاقات الشخصية معلومات إضافية يستفاد منها في تحسين الأداء الوظيفي ؟ 3_ هل تساهم العلاقات الشخصية في تنمية روح التعاون لدى الأفراد ؟ 4_ ما مدى مساهمة نسق العلاقات الشخصية في تحسين نوعية الأداء الوظيفي ؟ وقد اعتمادنا في هذه الدراسة الوصفية على المنهج الوصفي وعلى الاستمارة كأداة أساسية ، وعلى عينة قد شملت 35 مفردة من الإفراد العاملين بمؤسسة النقل و الجر بالسكك الحديدية وقد توصلنا في هذه الدراسة إلى النتائج التالية : نجد أن العلاقات الشخصية مع الزملاء في مؤسسة النقل والجر بالسكك الحديدية سوق أهراس أهمية كبيرة في تجسيد روح الانتماء للفرد فمن خلالها يشعر بتقدير الذات , كما أن العلاقات الشخصية في ما بينها تساهم في كسب الثقة بالنفس لدى العامل ذلك راجع لان الاتصال مع الزملاء و إبراز الفرد لذاته و مناقشته لمسائل العمل مع زملائه من خلال إنشاء روابط شخصية يكسب بها ثقة الزملاء و المسؤولين فعندما يجد الأذان الصاغية و التفاعل المتبادل من طرف الأفراد ، و أن العلاقات الشخصية تعمل على تنمية روح التعاون بين الأفراد وذلك من خلال تناسب هدف الجماعة مع هدف الفرد والانسجام والتناغم بين أفراد التنظيم و دينامكية الجماعة وهذا راجع إلى الغاية الواحدة للتنظيم فإذا كانت العلاقات الشخصية موجهة لخدمة أهداف الشركة ، وهذا يعتبر بعد إنساني يعمل على دعم وتقوية العلاقات وتحقيق الرضا الوظيفي . أما البعد الفني و التقني يتبين من خلال : أن العلاقات الشخصية تساهم في ربح الوقت وتحقيق سرعه أكثر في الأداء وذلك راجع إلى أن العلاقات الشخصية مع الأصدقاء والزملاء لا تخضع إلى شروط وقيود أنها تتجاوز السلم الهرمي و مستويات الإدارية والرسمية التي قد تعيق أحيانا سرعه انتقال المعلومات ، رغم ما توفره نسق العلاقات الشخص من تأثير على الأداء الوظيفي ليس بالضرورة أن يكون دائما ايجابيا فاستناد من المعلومات المتحصل عليها من طرف المبحوثين فأن العلاقات الشخصية ، لا توفر مناخ عمل ملائم لتحسين الأداء الوظيفي وذلك راجع إلى حصول جو من الفوضى الانشغال بالمسائل لشخصية و إهمال الهدف المراد تحقيقه وهذا قد يؤثر بالسلب على عملية الأداء الوظيفي للفرد داخل التنظيم. وخلصت هذه الدراسة إلى جملة من التوصيات التي أبرازها: _ تفعیل الاتصال غیر الرسمي في إطار الحدود التي یشغلها. _ تحقیــق التكامــل بــین الاتصــال الرســمي والاتصــال غیــر الرســمي والاســتفادة منهمــا فــي إیصال المعلومات الصحیحة بین العمال. _ الاسـتفادة مـن بعـض مزایـا الاتصـال غیـر الرسـمي خاصـة فیمـا یخـص المعلومـات التـي تخــص العمـــال، التــي یعتمـــد علیهـــا المســؤول المباشـــر فــي توجیهاتـــه وتعاملاتـــه ورؤیتـــه الإستراتیجیة . _ الاعتمـاد علـى الاتصـال غیـر الرسـمي فـي بنـاء العلاقـات بـین المسـؤول والعمـال وذلـك بالقضـــاء علــى بعــض العراقیــل التــي یحـــددها الاتصـــال الرســـمي ومحاولـــة المســؤول مــن الاستفادة من هذه العلاقات في إطار أهداف المؤسسة. كــذلك بالاتصــال غیــر الرســمي یعــرف المســؤول حقیقــة المعلومــات حــول العمــال فلقــاء العامل بالمسؤول في إطار غیـر رسـمي یوضـح الكثیـر مـن الانطباعـات التـي یكنهـا العامـل اتجاه المؤسسة وذلك من خلال الاقتراحـات التـي یقـدمها العامـل للمسـؤول والتـي تسـاهم فـي تحسين الاداء الوظيفي . _ محاولة إكتشاف قادة الإتصال غير الرسمي و العمل معهم عندما تتطلب الظروف ذلك لتغذية الإتصال غير الرسمي بالحقاىق حتى يتوفر لديها شيء مفيد تنقله بدلا من البيانات الضارة و الشائعات وجعله مساهم في تحسين أداء التنظيم لا عائقا لها . ----------------------------------------------
Keywords: الإتصال غير الرسمي، الأداء الوظيفي، الفرد